2016
DOI: 10.3892/br.2016.584
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of one-stage surgery to reconstruct bone defects using the modified Masquelet technique with degradable calcium sulfate as a cement spacer: A case report and hypothesis

Abstract: Abstract. In addition to autologous bone graft, vascularized fibular autograft and Ilizarov bone transfer, the Masquelet technique is another effective method to reconstruct bone defects. This technique was initially proposed in 1986 and consists of two stages. At the first stage, radical debridement is required and subsequently, a polymethylmethacrylate (PMMA) cement spacer is implanted at the site of the bone defects. At the second stage, when the PMMA-induced membrane is formed 6-8 weeks later, the cement s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…It has also been widely used in clinic as a local antibiotic carrier for the treatment of chronic osteomyelitis, because it is totally absorbed over a period of several weeks, releasing the entire antibiotic load 19 . We found that it also induced formation of membrane-like structure in clinical cases 20 , but the histological and biochemical characteristics of the CS-induced membrane were unclarified. There has been no research addressing these problems as well as the differences between the PMMA-induced versus the CS-induced membranes in repair of large segmental bone defects.…”
Section: Introductionmentioning
confidence: 73%
“…It has also been widely used in clinic as a local antibiotic carrier for the treatment of chronic osteomyelitis, because it is totally absorbed over a period of several weeks, releasing the entire antibiotic load 19 . We found that it also induced formation of membrane-like structure in clinical cases 20 , but the histological and biochemical characteristics of the CS-induced membrane were unclarified. There has been no research addressing these problems as well as the differences between the PMMA-induced versus the CS-induced membranes in repair of large segmental bone defects.…”
Section: Introductionmentioning
confidence: 73%
“…More recently, Nan Jing et al. [86] modified the traditional Masquelet technique, which has been widely used in treating massive bone defects, by using calcium sulfate to replace the PMMA as cement spacer, so as to make this technique a one-step surgery. In this case report regarding the reconstruction of an open fracture of the calcaneus at right foot, they found the formation of the induced membrane with the implantation of calcium sulfate by X-ray image and a computed tomography scan.…”
Section: Bone Grafts and Substitutes For Bone Defect Treatmentsmentioning
confidence: 99%
“…In this case report regarding the reconstruction of an open fracture of the calcaneus at right foot, they found the formation of the induced membrane with the implantation of calcium sulfate by X-ray image and a computed tomography scan. But this trial was then stopped by the patient and the calcium sulfate was finally replaced by autologous iliac crest bone grafts, and further characterization on the induced membrane and bone regeneration became impossible [86] .…”
Section: Bone Grafts and Substitutes For Bone Defect Treatmentsmentioning
confidence: 99%
“…After approximately four or eight weeks, a bone substitute, generally an autologous bone graft that includes all of the possible limitations mentioned above, is placed. Since the first study, the Masquelet technique has been widely used and modified with the development of new technologies to solve massive bone defects, while maintaining its clinical efficacy [ 10 , 11 , 12 ]. In a similar way, in the last few decades, the rigid, osteoconductive, and non-resorbable barrier membranes are used as part of regenerative treatments, and bone augmentation therapies have been thoroughly researched [ 13 ] as additional methods to improve osteoinduction and cell differentiation mechanisms [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%